QUALITY OF LIFE OF PATIENTS WITH METABOLIC SYNDROME IS IMPROVED AFTER WHOLE BODY VIBRATION EXERCISES - Carvalho-Lima, Rafaelle Pacheco; Sá-Caputo, Danúbia C.; Moreira-Marconi, Eloá; Dionello, Carla; Paineiras-Domingos, Laisa Liane; Sousa-Gonçalves, Cintia Renata; Morel, Daniele Soares; Frederico, Eric Heleno; Neves, Mario F.; Oliveira, Ricardo; Oigman, Wille; Marin, Pedro J.; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Whole body vibration exercises (WBVE) improve the quality of life (QoL) of different populations. Metabolic syndrome patients (MetS) may be favored by physical activity. Questionnaires are used to assess the QoL. The aim was to evaluate the QoL of patients with MetS that have undergone WBVE with a brief WHOQOL (WHOQOL-BREF). Material and Methods: MetS patients were randomly divided into three groups: (i) control group (CG), (ii) treated with WBVE once per week (WBVE1) and (iii) treated with WBVE twice per week (WBVE2). In the first session, the patient was sat in a chair in front of the platform with the feet on its base in 3 peak to peak displacements (2.5, 5.0 and 7.5 mm) and frequency of 5 Hz was used. From the second to the last session, patients were subjected to the same protocol, however they were standing on the base of the platform and the frequency was increased up to 14 Hz. The patients fulfilled the WHOQOL-BREF before the first and after the last sessions. Cronbach coefficients were determined to each domain of the WHOQOL-BREF and test Wilcoxon (p<0.05) was used. Results: The patients of the WBVE1 group had improvements in the physical, psychological and environment domains while in the WBVE2, the improvements were in the physical and social relationships domain of the WHOQOL-BREF. Conclusion: It was observed that the WBVE in a protocol (one or two times per week) with a progressive and increased frequency improves the QoL of patients with MetS in different domains of the WHOQOL-BREF.